Relationship between emotional intelligence and commitment to change among senior administrative and diplomatic service (ADS) officers in Malaysia - Ramly Mohd Sabri, Mansor Mahaliza (Universiti Pendidikan Sultan Idris, 2017)
Relationship between emotional intelligence and commitment to change among senior administrative and diplomatic service (ADS) officers in Malaysia by Ramly Mohd Sabri, Mansor Mahaliza,